Assessment of the environmental status in Hellenic coastal waters (Eastern Mediterranean): from the Water Framework Directive to the Marine Strategy Water Framework Directive. - N. SIMBOURA; M. TSAPAKIS; A. PAVLIDOU; G. ASSIMAKOPOULOU; K. PAGOU; H. KONTOYANNIS; C. ZERI; E. KRASAKOPOULOU; E. ROUSSELAKI; N. KATSIARAS; S. DILIBERTO; M. NALETAKI; et al. (Mediterranean Marine Science, 2014)
A methodology is presented to assess the environmental status sensu the Marine Strategy Water Framework Directive (MSFD) based on data obtained from the monitoring of water quality in the Hellenic coastal waters within the Water Framework Directive (WFD). An adapted decision tree used for integrating the results of the WFD in the Basque country was applied. Modifications lie to the evaluation of the physicochemical status based on a eutrophication index developed for Eastern Mediterranean waters. Results on hydromorphological, physicochemical and biological elements are presented. The chemical status was evaluated based on measurements of heavy metals in water. The evaluation of the biological quality was based on the use of metrics developed for phytoplankton biomass, benthic macroinvertebrates and macroalgae updated to accommodate MSFD needs. Results on the integrative status of the water bodies were validated by correlating classification results with a pressure index and environmental indicators in water column and sediment. Following this decision tree the majority of stations expected to be at risk of achieving the good status were found in moderate status. Benthos was found to be the element with the closest agreement with the integrated final status having an increased weighting in the decision tree. The quality of benthos and in some limited cases the eutrophication index determined largely the final status. The highest disagreement with the integrative classification was produced by macroalgae. All indicators used correlated with water and sediment parameters but benthos correlated better with sediment factors while phytoplankton and eutrophication index with water column parameters.